Contaminated land - Tromans, Stephen; Turrall-Clarke, Robert (Sweet & Maxwell, 2008)
Provides guidance on principles and best practice when drafting and reviewing lifetime trusts and will trusts under Jersey and Guernsey law. Enables practitioners to interpret and understand existing trusts, and be able to draft new ones. Includes precedents which are also on an accompanying CD